Assessment of Levels of Complement Factors C3 and C4 in Lupus Nephritis Flare in Resource Limited Setup - Ali Talal, Zahid Rafique, Azhar Nasim, Aurangzeb Afzal, Asmara Asrar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Renal biopsy, an invasive and costly procedure, is required to diagnose lupus nephritis. In some studies, complement levels C3 and C4 are being utilized as a diagnostic tool to distinguish whether active urine sediment, rising proteinuria and loss of renal function are attributable to systemic lupus erythematosus (SLE) activity or other non-immunological causes. Aim: To find out the frequency of altered levels of complement factors C3 and C4 in lupus nephritis with nephric or proteinuric flare. Methods: The present observational study was conducted in the Department of Nephrology, Services Hospital, Lahore. A total of fifty patients of lupus nephritis showing proteinuric, nephritic or mixed flare were enrolled. Demographics and clinical parameters were noted and C3 and C4 levels were measured. Both males and females were included in the study. This study was approved by the Institutional Review Board of the Services Institute of Medical Sciences. Results: Out of a total of 50 patients, 19 were males while 31 were females. The mean age of the patients was 29.40 ± 6.66 years. Low levels of complement factor C3 were discovered in 12(24%) of the patients, whereas low levels of complement factor C4 were detected in 18(36%) of the patients. Proteinuric flare was found in 17 patients, nephritic flare in 25 patients whereas both types of flare were found in a total of 8 patients. Conclusion: One-third of the patients with nephritic type flare of lupus nephritis had low levels of C3 or C4 in our study. Further studies with larger sample size are needed to assess the potential of complement levels C3 and C4 as tools to diagnose lupus nephritis flare.